PEMBELAJARAN PERSEN DENGAN MENGGUNAKAN MEDIA DOWNLOAD BAR PADA SISWA KELAS 5 SEKOLAH DASAR - Wuli Oktiningrum (Universitas Pendidikan Indonesia, 2021)
Abstract:. This research was conducted on class V students of SD Negeri 179 Palembang, with the aim of knowing students' understanding of the percent material by using media download bars. The subjects in this study were 28 students with heterogeneous abilities. The research methodology used in this study is Design Research with a Realistic Mathematics Education (RME) approach. This study fulfilled five characteristics of RME, namely the use of laptops, computers and downloads of the internet (using of context), pictures of download bars (use of models), activities in LKK (pupil own creations and contributions), presentation and group discussion (interactivity) and problems change fractions into percent (intertwining). The results of this study indicate that students have been able to solve the percent problem by using media download bars.Keyword: Download Bar, Percent, RME, Design Research Abstrak: Penelitian ini dilakukan pada siswa kelas V SD Negeri 179 Palembang, dengan tujuan mengetahui pemahaman siswa pada materi persen dengan menggunakan media download bar. Subjek pada penelitian ini sebanyak 28 siswa dengan kemampuan yang heterogen. Metodologi penelitian yang digunakan pada penelitian ini adalah Design Research dengan pendekatan Realistic Mathematics Education (RME). Penelitian ini telah memenuhi lima karakteristik RME yaitu penggunaan laptop, computer dan download di internet (using of context), gambar bar download (penggunaan model), kegiatan pada LKK (pupil’s own creations and contributions), presentasi dan diskusi kelompok (interactivity) dan masalah merubah pecahan kedalam bentuk persen (intertwining). Hasil penelitian ini menunjukkan bahwa siswa telah mampu menyelesaikan soal persen dengan menggunakan media download bar.Kata Kunci: Download Bar, Persen, RME, Design Research